Factores de riesgo asociados a depresión en pacientes con enfermedad renal crónica terminal que reciben hemodiálisis en un hospital de Loreto 2022 - Romero Chavil, Bertha Nicolaza (2023)
Objectives: The main objective was to determine the risk factors associated with depression in patients with CKD receiving hemodialysis in a Loreto Hospital in 2022. Materials and methods: Analytical case-control study, including 87 patients with CKD who received hemodialysis in HRL 2022, selected by random evidence in 36 cases and 36 controls (yes depression and no depression). A validated collection instrument was transmitted, the patient's information was obtained through a census survey and some data on the causative pathologies was corroborated with the clinical history. An observational, multivariate, cross-sectional analysis was performed to determine the association between risk factors and depression in ERTC patients. Results: The risk factors associated with depression in the multivariate analysis of the study include non-occupation (p=0.029; OR=3.504; IC=1.094-11.223), deficient family support (p=0.016; OR=3.353; IC=1.235-9.102) and poor sleep quality (p=0.006; OR=7.480; CI=1.521-36.778) are statistically significant, so the association is accepted, therefore they behave as risk factors. Conclusions: In the multivariate analysis of this study, we found non-occupation, deficient family support, and poor quality of sleep as risk factors.